Residency, movements and habitat use of adult white seabream (Diplodus sargus) between natural and artificial reefs - Abecasis, D. (2016)
Artificial reefs are used as management tools for coastal fisheries and ecosystems and the knowledge of habitat use and fish movements around them is necessary to understand their performance and improve their design and location. In this study wild specimens of Diplodus sargus were tagged with acoustic tags and their movements were tracked using passive acoustic telemetry. The monitored area enclosed a natural rocky reef, an adjacent artificial reef (AR) and shallower sandy bottoms. Most of the fish were close to full time residents in the monitored area. Results revealed that D. sargus use the natural reef areas on a more frequent basis than the AR. However, excursions to the adjacent AR and sandy bottoms were frequently detected, essentially during daytime. The use of acoustic telemetry allowed a better understanding of the use of artificial reef structures and its adjacent areas by wild D. sargus providing information that is helpful towards the improvement of AR design and location. (c) 2013 Elsevier Ltd. All rights reserved.